Evaluating Judicial Education Organizations. - (:unkn) unknown (My University, 2016)
This paper seeks to provide an analytical framework that may be used to evaluate a judicial education organization (referred to in this paper as a judicial academy). It is meant to be complementary to my colleague Tom Langhorne’s paper on evaluation of judicial education programming. It describes issues in addition to programming that determine the programme impact and the realization of judicial education objectives.